Stocks vs Mutual Funds in An Election Year: Which is More Profitable? - Leonny Noviyana Sakti Pamungkas; Y Anni Aryani; Doddy Setiawan (Riset Akuntansi dan Keuangan Indonesia, 2025)
This study analyzes the reaction of stock markets and mutual funds to political events using a sample of 15 countries that held elections. In general, we document the returns before and after the elections and use t-test to determine the effect and f-test to measure the volatility of both. The results show that the short-term effect is significant for all mutual funds and only a few stocks are significant. In addition, with the same conditions, it does not necessarily have the same impact on the two instruments.  However, we only found the short-term impact. While the explanation is not too clear, investors may want to observe the economic impact on stocks and mutual funds arising from longer time horizons.